Synthesis of Indole-Based Derivatives Containing Ammonium Salts, Diamines and Aminoureas for Organocatalysis - Marcello Casertano; Brian G. Kelly; Malachi W. Gillick-Healy; Paolo Grieco; Mauro F. A. Adamo (Organics, 2025)
Indole heterocycles have an established reactivity, and these compounds are H-bond donors via a peculiar non-basic NH. However, the indole core has been scarcely employed in organocatalysis, with only a few examples relevant to electrophilic halogenation reported. To expand the range of potential transformations achievable via indole catalysis, we have designed a set of new organic species incorporating an indole core, alongside three privelaged chiral moieties found in many known organocatalysts, namely a quaternary ammonium salt, a diamine and an amino-urea. Herein, we report an optimised synthetic route for the preparation of these potential catalytic species in an enantiomerically pure form. The syntheses are conceived to be modular and therefore will allow each of the three single organic catalysts to be expanded into families without alteration of the synthetic layout, therefore leading to a fast optimisation of new asymmetric procedures.